ACTUALIZATION OF THE NOTION OF «HUMAN VIABILITY» AS A KEY CATEGORY OF MODERN PSYCHOLOGY - Kovalchuk, Anna (PSYCHOLOGICAL JOURNAL, 2019)
The article deals with the consideration of the essence of viability, one of the most relevant psychological category. It is understood as the ability of a person to manage the resources of his / her own health and the socially acceptable way to use for this family, society, culture (according to M. Ungaro); as a systemic quality of a person characterising the organic unity of an individual’s human and sociopsychological abilities to realise the resource potential, using constructive behavioural strategies in difficult life situations and in conditions of socioeconomic deprivation, which ensures that the individual returns to the pre-crisis level of functioning and determines post-crisis personal growth (according to A. Nesterova). The psychological category of vitality has terms related to it, among which are: 1) mental health of a person is a person’s own vitality, life force, which is ensured by the full development and functioning of the mental apparatus; 2) life self-realization is a form of self-organisation in the process of its formation, which determines the intentionality of movement and the ability to interact with the world for the realisation of life choices; 3) sustainability is the result of dynamic equilibrium (balance) between risk factors and protection factors, which are determined by individual human qualities and features of the external environment, and also represent a certain risk; 4) “feeling of connectedness” is characterised by three main points: a) the stimuli of the external and internal environment are clear and understandable; b) a person is able to control the situation, which is formed by these incentives; c) due to the human awareness of the meaning of events, they are perceived as a challenge, requiring acceptance and a decent response, and therefore are not felt as an unbearable burden; 5) adaptation is a targeted systemic reaction of the body to long-term and multiple, intense and extensive environmental effects that lead to disruption of the homeostatic balance; 6) regulation is the state of harmony between internal needs and external requirements, as well as a set of processes that are used to achieve this state; 7) stability phenomenon is the special pattern of the structure of the installation and skills, which allows you to turn your own changes into realistically realised opportunities, such as the basis on which stress effects are processed. The notion of “vitality” has the following unrelated terms: 1) “victimhood” is a set of human properties that contribute to the maladaptive style of response of the subject, which leads to damage to his / her physical or emotional-mental health; 2) “psychological helplessness”, which appears in two main varieties of “learned helplessness” and “personal helplessness”.